Mental health services and late-onset depression - McGill Fox, Eileen (Kansas State University, 2009)
As the number of Americans aged 60 and over increases substantially in the coming years, so is the incidence of depression among this age group. The purpose of this report is to explore the mental health needs of older Americans, the ways in which they are undiagnosed or under-diagnosed for depression, the clinical challenges associated with treating depression in the elderly, and the barriers that are in place due to social, psychological, financial and governmental factors. With the “Baby Boom” generation (those born between 1946-1964) entering their senior years, there will be an increased need for Marriage and Family Therapists to be cognizant of the rise in depression and familiar with the treatment options and limitations. Marriage and Family Therapists adhere to the Systems Theory and thus are uniquely qualified to act as a bridge between the medical and mental health communities. This report will promote the collaborative approach to healthcare and the way in which Marriage and Family Therapists can contribute to the treatment of depression in the aged.
Keywords: Depression; Late onset; Gerontology (0351); Health Sciences, Mental Health (0347)